Whistleblowing in the Australian Public Sector Enhancing the theory and practice of internal witness management in public sector organisations - Brown, A. J. (Australia and New Zealand School of Government (ANZSOG), 2008)
Of the many challenges in public sector management, few are as complex as the management of whistleblowing. Because it can lead to the discovery and rectification of wrongdoing, public interest whistleblowing is widely acknowledged as being positive for organisations and for society at large. However, the conflicts and reprisal risks often associated with whistleblowing also support a widespread belief that every whistleblower is destined to suffer, and nothing can be done to protect them from reprisals. Even if they did it once, sensible employees are often seen as unlikely to ever blow the whistle a second time around. The extensive research in this book reveals a more complex and, fortunately, more positive picture. The product of one of the world's most comprehensive research projects on whistleblowing, evidence from over 8,000 public servants in over 100 federal, state and local government agencies shows that whistleblowers can and do survive, and that often their role is highly valued. Public sector managers face significant challenges in better managing and protecting whistleblowers. There is great variation between the many public agencies making the effort, and the many agencies where the outcomes - for managers and whistleblowers alike - are still likely to be grim. This book is compulsory reading for all public sector managers who wish to turn this negative trend around, and for anyone interested in public accountability generally.